Efficient modulation of the catalytic performance of electrocatalytic nitrogen reduction with transition metals anchored on N/O-codoped graphene by coordination engineering. Issue 3 (24th December 2021) - Wang, Xiaolin; Yang, Li-Ming
Abstract : Several efficient catalysts for eNRR from a large family of transition metal anchored N/O-codoped graphene were uncovered via coordination engineering, high-throughput screening and first-principles calculations. Abstract : We for the first time report the discovery of a series of highly efficient electrocatalysts, i.e., transition metals anchored on N/O-codoped graphene, for nitrogen fixation via high-throughput screening combined with first-principles calculations. The catalytic performance can be effectively modulated by coordination engineering. Among 10 representative electrocatalysts ( i.e., V–N4 @Gra, Tc–N4 @Gra, V–O1 N3 @Gra, V–O2 N2 α @Gra, V–O2 N2 β @Gra, V–O2 N2 γ @Gra, V–O3 N1 @Gra, Mo–O3 N1 @Gra, V–O4 @Gra and Ru–O4 @Gra), V–O2 N2 γ @Gra possesses the lowest Δ G max of 0.38 eV. Molecular dynamics simulation results indicate that all the predicted TM–O x N y @Gra ( x + y = 4) have high stabilities and can be used as electrocatalysts under practical reaction conditions. The more charge on the adsorbed N2, the longer the N–N bond length and the greater the activation of N2 . Interestingly, the linear combination of adsorption energy of different intermediates, i.e., Δ E ads [(*N2 − *N) + (*NNH − *N) + (*NH2 − *N)], can be used as a good descriptor to unveil the structure–property relations, and V–O2 N2 γ @Gra possessed moderate adsorption energy, so it exhibits the highest catalytic activity for the electrocatalytic nitrogen reduction reaction (eNRR) among all investigated materials. Overall, through coordination engineering, the coordination environment and electronic structure of the active centers can be modulated properly, thereby regulating the catalytic activity effectively. We expect that our work will provide new insights into the rational design of electrocatalysts and effective modulation of the catalytic performance via coordination engineering. The present study opens up an important route for the development of efficient catalysts for the eNRR, and will inspire the follow-up experimental and theoretical efforts in this direction.